THE EFFECT OF LP AND CS ON COMPANY VALUE WITH CSR AS A MODERATING VARIABLE IN PROPERTY AND REAL ESTATE COMPANIES - Siti Dini; Rehulina Octavia Br. Sitepu; Silviani Gulo; Adri Josua Karunia Naibaho; Ratna Sari Dewi (Jurnal Ipteks Terapan, 2023)
One of the prospective investment facilities is property and real estate so that investors are interested in investing their funds in these businesses. The limited supply of land and buildings as the population increases and demand increases, land and real estate prices rise every year thereby increasing the welfare of shareholders by increasing the value of the company. However, the increase is inversely proportional to the value of the company. The purpose of this research is to see profitability, leverage, company size influence or not on firm value with CSR as a moderating variable. Sampling method with purposive sampling method. The data analysis method used is multiple linear regression analysis and moderating regression analysis (MRA). The results of this study indicate that partially profitability and firm size have a positive and significant effect on firm value while leverage has no positive and insignificant effect on firm value. And CSR as a moderating variable cannot moderate the relationship between profitability, leverage and firm size on firm value